Slow Is Also Fast: Feedback Delay Affects Anxiety and Outcome Evaluation - Zhang, Xukai; Lei, Yi; Yin, Hang; Li, Peng; Li, Hong (Frontiers in Human Neuroscience, 2018)
Performance-related feedback plays an important role in improving human being’s adaptive behavior. Using event-related potentials (ERPs), previous studies have associated a particular component, i.e., reward positivity (RewP), with outcome evaluation processing and found that this component was affected by waiting time before outcome evaluation. Prior research has also suggested that anxious individuals are more prone to detecting threats and susceptible to negative emotions, and show different patterns of brain activity in outcome evaluation. It is quite common that a decision-maker cannot receive feedback immediately; however, few studies have focused on the processing of delayed feedback, especially in subjects who exhibit trait anxiety. In this study, we recruited 2 groups of subjects with different trait anxiety levels and recorded ERPs when they conducted a time-estimation task with short (0.6 to 1 second) or long delayed (4 to 5 seconds) feedback. The ERP results during the cue phase showed that long waiting cues elicited more negative waves than short waiting cues in the high trait anxiety (HTA) group. More importantly, the 2 groups showed different patterns of ERP in the feedback condition. In the low trait anxiety (LTA) group, larger RewP was found in the short-delayed than in the long-delayed condition. In contrast, no difference was found in the HTA group. This pattern may reflect the hyperactivity of the reward systems of HTA individuals in uncertain environments (e.g., the long-delay condition) compared with LTA individuals. Our results provide a direction for future research on the neural mechanisms of reinforcement learning and anxiety.